The Effectiveness of the Demonstration Method to Improve Student Learning Outcomes - Rohmat Umara (East Asian Journal of Multidisciplinary Research, 2022)
This research is motivated by the fact that most students find it difficult to learn science so they don't like it. From the results of preliminary observations, obtained several things that are not in accordance with the fulfillment of quality learning for grade 6 students at SD Negeri 1 Cikeris Purwakarta Regency, namely: (1) The learning activities carried out have not provided a learning experience for students who require excessive challenges to optimize the development of thinking skills, creativity, problem solving skills, experimentation, innovation, discovery, development of interests, talents and skills. (2) In the delivery of learning, the teacher does not attract the attention of students. Among them are not using learning methods that are less precise and less varied, as well as the lack of utilization of media and learning resources from the environment, resulting in low student learning outcomes.